Historic Charleston - Abbot, Shirley (Birmingham, AL Oxmoor House, Inc., 1988)
D., 8/99
Keywords: Charleston (S. C.)--Dwellings; Historic buildings--South Carolina--Charleston; Architecture, Georgia--South Carolina--Charleston